Thermophiles : the keys to molecular evolution and the origin of life? - Wiegel, Juergen; Adams, Michael W. W., 1954- (Taylor & Francis, 1998)
Late-1990s developments in the study of thermophiles have had considerable significance on theories of evolution. Scientists have begun to study their biology in an attempt to provide clues about the beginnings of life on our planet.